Short Communication: A new record of naturalized Selaginella uncinata (Desv.) Spring (Selaginellaceae) from Java, Indonesia - AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2014)
Setyawan AD. 2014. A new record of naturalized Selaginella uncinata (Desv.) Spring (Selaginellaceae) from Java, Indonesia. Biodiversitas 15: 261-268. During extensive field researches on the diversity and distribution of Selaginella in Java, between 2007 and2014, an alien species has been found in nature, i.e. Selaginella uncinata. This species is a trailing herb with small, wiry, creeping mainstem, fan-shaped branches, rooting at the nodes to c.a. 100 cm long or more; leaves are dimorphic, 4-ranked, and characterized byconspicuous blue iridescent; strobili are tetragonal, up to c.a. 2 cm long. S. uncinata was found growing wild in the highlands with highrainfall, namely: Cibodas Botanical Garden, Cianjur, West Java and Tawangsari, in the city district of Wonosobo, Central Java,Indonesia. Transplant experiments showed that this plant was able to grow and reproduce well in lowlands (Depok, 107 m asl.) andhighlands (Wonosobo, 768 m asl.). In the experimental garden, it could compete successfully with native species of Javan selaginellas, for space, sunlight and nutrients. Therefore, we must be concerned about the invasion ability of this species.